Strategi Meningkatkan Partisipasi Masyarakat dalam Pembangunan Desa yang Berkelanjutan - Sari, Nurmita; Parawu, Hafiz Elfiansya; Taufik, Ahmad (Department of Public Administration, Muhammadiyah University of Makassar, 2024)
Community participation in village development is essential to achieve sustainable and inclusive development. When communities are actively involved in the development process, they feel ownership and responsibility for the results achieved. This research aims to analyse strategies to increase community participation in the development of Ilan Batu Uru Village, West Walenrang Sub-district, Luwu Regency. The research method used in this research is a qualitative research method, which is a form of research that aims to understand and describe phenomena about strategies to increase community participation in village development by analysing behaviour, perceptions, interests, motivations, actions, by presenting data in a description in the form of words or language. The results show that the strategy of increasing community participation in increasing community participation is good enough. However, it needs to be improved to be more optimal, this can be seen from the aspects of planning, implementation and supervision.